TANTANGAN BERIMAN DI TENGAH PENGARUH DENOMINASI PROTESTAN Tinjauan Kritis Studi Kasus Pindah Agama Remaja Katolik Paroki St. Gabriel Nunukan - Fredirikus Nono (Aggiornamento, 2022)
This study will discuss how St. Gabriel Nunukan Parish Catholic youth maintain their catalytic faith amid the currents of the world today. The focus of this research was the case of the transfer of several Catholic teenagers to protestant church denominations that occurred in the parish of St. Gabriel Nunukan. The research uses the Blanded methodology, qualitative-quantitative. The authors collect data by means of interviews and disseminate questionnaires. The author also interviewed several teenagers who have now renounced the Catholic faith and moved to other Churches. Based on the research, the authors found that Nunukan Catholic teenagers are faced with a variety of challenging challenges of the faith. Those who are temporarily in a period of self-discovery must deal with the general environment and the times that offer various forms of worldly pleasure. The various challenges of faith they face include the influence of social media, promiscuity, juvenile delinquency, early marriage, drugs, and also conversion. One of the serious problems faced in the Church especially for Catholic youth in Nunukan is the rise and development of the denomination of the Prostestan Church. Here the Church is also required to take a surefire model of assistance for adolescents so that they are able and faithful to maintain their faith. The Church can overcome this through holistic assistance.